Marqueurs du point de départ spatial et temporel antéposés : une comparaison de depuis, dès et à partir de - Véronique Lagae (Corela)
The main purpose of this paper is to refine the analysis of French adverbials expressing a temporal or a spatial starting point. It focuses more specifically on their ability to function as discourse frames when placed in sentence-initial position. A corpus-based study of prepositional phrases headed by the prepositions à partir de, depuis et dès demonstrates that, due to their dynamic nature, specific difficulties arise for each one of them with regard to discourse framing. Hence it is proven useful to differentiate between frames with a semantic scope (‘strong’ frames) and frames with a mere textual scope (‘weak’ frames).